Habitat associations of young Black Grouse Tetrao tetrix broods. Issue 2 (2nd April 2016) - Roos, Staffan; Donald, Chris; Dugan, Desmond; Hancock, Mark H.; O'Hara, David; Stephen, Leigh; Grant, Murray
ABSTRACT: Capsule: In the Scottish Highlands, Black Grouse Tetrao tetrix females with young broods selected areas rich in wet flushes, grasses and Sphagnum mosses. Aims: To identify associations between young Black Grouse broods and habitat characteristics. Methods: We located brood-rearing Black Grouse females in four areas of moorland-forest mosaic in the Scottish Highlands. Each brood was paired with a random reference location 100 m away. We recorded cover of different habitats and fine-scale vegetation and structure within squares of 1 and 0.25 ha, respectively. Associations between brood occurrence and habitat and vegetation variables were examined at the two scales. Results: Black Grouse broods were positively associated with wet flushes (1 ha), and with Heather Calluna vulgaris, sedges Carex spp., grasses, Sphagnum mosses and taller vegetation with intermediate levels of height variability (0.25 ha). Conclusions: This study highlights the importance of wet habitats for young Black Grouse chicks. In addition, relatively tall field-layer vegetation comprising Heather, sedges, grasses over a layer of Sphagnum mosses attracted brood-rearing Black Grouse females. Many management practices associated with peatland restoration, including drain-blocking, Sphagnum re-establishment and the avoidance of burning on deep peat soils, are therefore consistent with favourable habitat management for Black Grouse.